FORTAX: UK tax and benefit system documentation - Jonathan Shaw (Institute for Fiscal Studies (IFS), 2011)
This document describes the UK tax and benefit system between April 1990 and April 2010, as implemented in FORTAX, a microsimulation library written in Fortran. It begins with an overview of FORTAX and the information it calculates. Subsequent sections describe the taxes and benefits implemented in FORTAX, noting where simplifications have been made. An appendix lists values of the major tax and benefit parameters over time.
Keywords: 330; Steuersystem; Sozialpolitik; Datenbank; Großbritannien